7th International Symposium on Superalloy 718 and Derivatives (2010) 2010
DOI: 10.7449/2010/superalloys_2010_307_319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Strain during Forging on Subsequent Delta Phase Precipitation during Solution Annealing in ATI 718Plus® Alloy

Abstract: ATI 718Plus ® alloy relies upon grain boundary precipitation of the delta phase in order to achieve good resistance to notch failure. Delta phase precipitation can occur when forging at subsolvus temperatures or during solution annealing. Precipitation of delta phase during solution annealing can be affected by the interaction of forging temperature and strain during hot working whereby the combination of high forging temperature and low strain can result in unsatisfactory delta phase precipitation. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Similar to Inconel 718, increasing the level of strain also causes increased η phase precipitation within ATI 718Plus [54,55]. Casanova et al [56] found that within the microstructure of components made with ATI 718Plus, two main morphologies co-exist together; coarse plates and thin lamellae, and the origin of these were investigated by the author.…”
Section: Effect Of Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to Inconel 718, increasing the level of strain also causes increased η phase precipitation within ATI 718Plus [54,55]. Casanova et al [56] found that within the microstructure of components made with ATI 718Plus, two main morphologies co-exist together; coarse plates and thin lamellae, and the origin of these were investigated by the author.…”
Section: Effect Of Strainmentioning
confidence: 99%
“…However, it would be of interest to obtain experimental volume fraction data at lower temperatures to see if these discontinuities can be validated. McDevitt [54] investigated the effect of thermomechanical processing on η phase precipitation in ATI 718Plus, and found that the kinetics of precipitation are increased as the level of residual strain is increased. Casanova et al [57] also reached the same conclusion in that areas with higher levels of residual strain produced faster precipitation kinetics.…”
Section: Precipitation Kinetics Of Grain Boundary Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although relatively little literature exists regarding the effect of deformation on precipitation kinetics within nickel superalloys, some authors have found that increasing the level of strain also causes increased η phase precipitation within ATI 718Plus [13,14]. Casanova et al [15] found that within the microstructure of components made with ATI 718Plus, two main morphologies co-exist together; coarse plates and thin lamellae, and the origin of these were investigated by the author.…”
Section: Introductionmentioning
confidence: 99%